(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Manufacturing of "green" products, especially those utilized in renewable energy systems and clean technology equipment of all kinds. The “greening” of industry is accomplished by reducing renewable resource consumption, recycling and reusing trash, and decreasing emissions to minimize noise and waste. This article offers an overview of green manufacturing, including its overview and why it is needed, as well as green manufacturing methods that reduce waste and emissions. The present work focuses on ecological design for the environment, including energy efficiency and product production with reduced pollution. Further, author stresses the use of green manufacturing to produce a cleaner product that can be reused, resulting in a shorter product life cycle. An effort has been made to speak about sustainability accounting as well as green supply chain management. The main goal of green production is to preserve the planet while simultaneously reducing the product’s quality.